Ability of an alkali-tolerant mutant strain of the microalga Chlorella sp. AT1 to capture carbon dioxide for increasing carbon dioxide utilization efficiency. (November 2017) - Kuo, Chiu-Mei; Lin, Tsung-Hsien; Yang, Yi-Chun; Zhang, Wen-Xin; Lai, Jinn-Tsyy; Wu, Hsi-Tien; Chang, Jo-Shu; Lin, Chih-Sheng
Graphical abstract: Highlights: An alkali-tolerant Chlorella sp. AT1 grows well in pH 6–11 media. The optimal pH of the medium is 10 for the growth of the Chlorella sp. AT1 strain. Increasing pH of culture medium can elevate CO2 dissolution for microalgae growth. Higher CO2 fixation efficiency can be obtained by intermittent CO2 aeration. CO2 utilization efficiency aerated with CO2 intermittently in pH 11 medium was 20.4%. Abstract: An alkali-tolerant Chlorella sp. AT1 mutant strain was screened by NTG mutagenesis. The strain grew well in pH 6–11 media, and the optimal pH for growth was 10. The CO2 utilization efficiencies of Chlorella sp. AT1 cultured with intermittent 10% CO2 aeration for 10, 20 and 30 min at 3-h intervals were approximately 80, 42 and 30%, respectively. In alkaline medium (pH = 11) with intermittent 10% CO2 aeration for 30 min at 3-, 6- and 12-h intervals, the medium pH gradually changed to 10, and the biomass productivities of Chlorella sp. AT1 were 0.987, 0.848 and 0.710 g L −1 d −1, respectively. When Chlorella sp. AT1 was aerated with 10% CO2 intermittently for 30 min at 3-h intervals in semi-continuous cultivation for 21 days, the biomass concentration and biomass productivity were 4.35 g L −1 and 0.726 g L −1 d −1, respectively. Our results show that CO2 utilization efficiency can be markedly increased by intermittent CO2 aeration and alkaline media as a CO2 -capturing strategy for alkali-tolerant microalga cultivation.